How job characteristics influence healthcare workers’ happiness: A serial mediation path based on autonomous motivation and adaptive performance - Junça Silva, A.; Menino, C. (Sustainability, 2022)
Self-determination theory suggests that motivation is multidimensional; as such, there are various dimensions ranging from autonomous (i.e., intrinsic) to more controlled forms (extrinsic) of motivation. While intrinsic motivation appears to be positively related to an individual’s optimal functioning (e.g., happiness and performance), extrinsic motivation appears to be less beneficial. Furthermore, motivation is strongly determined by the context (e.g., job characteristics, such as autonomy). Although the relationship between job characteristics and workers’ motivation has been demonstrated, how it impacts performance and happiness is still to be unpacked. Moreover, it is relevant to analyze such models within healthcare workers; their work is emotionally and psychologically demanding, hence, understanding what drives their intrinsic motivation is of crucial importance. Thereby, the aim of the study was to analyze the mediating role of intrinsic motivation and adaptive performance on the relationship between job characteristics and happiness. Based on the job characteristics model, we proposed a serial path from motivating job characteristics (autonomy, feedback, variety, meaning, and task identity) to healthcare workers’ happiness via intrinsic motivation and adaptive performance, which was justified using the self-determination theory. We also argue that this path would not be significant for extrinsic motivation. We gathered data from 290 healthcare workers from a nursing home. The data were collected at three time points. The results support our hypotheses by demonstrating that all job motivating characteristics (autonomy, feedback, variety, meaning, and task identity) predicted healthcare workers’ happiness by enhancing their intrinsic motivation and leading to better adaptive performances. The results are not significant for extrinsic motivation; that is, the serial mediating path was not significant when extrinsic motivation was analyzed. The findings highlight the need for managers to focus on work design, in a way to promote certain job-motivating characteristics (e.g., autonomy), to improve healthcare workers’ motivation, which leads them to achieve more outstanding performances and, consequently, be happier. The study highlights that when healthcare workers have a job that provides them autonomy and regular feedback, with meaningful and varied tasks to which they feel a sense of identification, they tend to feel intrinsically motivated in their work, promoting higher adaptability to daily challenges, and, as a result, leaves them happier.